Selective T-Type Calcium Channel Block in Thalamic Neurons Reveals Channel Redundancy and Physiological Impact of I(Twindow) - Dreyfus, Fanny M. (Society for Neuroscience, 2010)
Although it is well established that low-voltage-activated T-type Ca(2+) channels play a key role in many neurophysiological functions and pathological states, the lack of selective and potent antagonists has so far hampered a detailed analysis of the full impact these channels might have on single-cell and neuronal network excitability as well as on Ca(2+) homeostasis. Recently, a novel series of piperidine-based molecules has been shown to selectively block recombinant T-type but not high-voltage-activated (HVA) Ca(2+) channels and to affect a number of physiological and pathological T-type channel-dependent behaviors. Here we directly show that one of these compounds, 3,5-dichloro-N-[1-(2,2-dimethyl-tetrahydro-pyran-4-ylmethyl)-4-fluoro-piperidin-4-ylmethyl]-benzamide (TTA-P2), exerts a specific, potent (IC(50) = 22 nm), and reversible inhibition of T-type Ca(2+) currents of thalamocortical and reticular thalamic neurons, without any action on HVA Ca(2+) currents, Na(+) currents, action potentials, and glutamatergic and GABAergic synaptic currents. Thus, under current-clamp conditions, the low-threshold Ca(2+) potential (LTCP)-dependent high-frequency burst firing of thalamic neurons is abolished by TTA-P2, whereas tonic firing remains unaltered. Using TTA-P2, we provide the first direct demonstration of the presence of a window component of Ca(2+) channels in neurons and its contribution to the resting membrane potential of thalamic neurons and to the Up state of their intrinsically generated slow (<1 Hz) oscillation. Moreover, we demonstrate that activation of only a small fraction of the T-type channel population is required to generate robust LTCPs, suggesting that LTCP-driven bursts of action potentials can be evoked at depolarized potentials where the vast majority of T-type channels are inactivated.